PENGARUH STRES KERJA, LINGKUNGAN KERJA NON FISIK DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PERAWAT - Tri Hadi Hardianto Saputra; Ibnu Hajar; Arsip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purposes of this study are (1). To find out and analyze whether work stress, non-physical work environment, and work motivation affect the job satisfaction of nurses in the Bahteramas Hospital Inpatient Room, Southeast Sulawesi Province during the Covid-19 Pandemic; (2) To find out and analyze whether work stress affects the job satisfaction of nurses in the Inpatient Room at Bahteramas Hospital, Southeast Sulawesi Province during the Covid-19 Pandemic; (3) To find out and analyze whether the non-physical work environment affects the job satisfaction of nurses in the Inpatient Room at Bahteramas Hospital, Southeast Sulawesi Province during the Covid-19 Pandemic; (4) To find out and analyze whether work motivation affects the job satisfaction of nurses in the Inpatient Room at Bahteramas Hospital, Southeast Sulawesi Province during the Covid-19 Pandemic. The analysis tool uses Multivariate Linear Regression with a sample of 98 respondents.The results showed (1) work stress, non-physical work environment, and work motivation had a positive and significant effect on the job satisfaction of nurses at the Bahteramas Regional General Hospital, Southeast Sulawesi Province, (2) work stress had a negative and significant effect on the job satisfaction of nurses at the Regional General Hospital. Bahteramas Southeast Sulawesi Province, (3) Non-Physical Work Environment has a positive and significant effect on the job satisfaction of nurses at the Bahteramas Regional General Hospital, Southeast Sulawesi Province, (4) Work motivation has a positive and significant effect on the job satisfaction of nurses at the Bahteramas Regional General Hospital, Southeast Sulawesi Province.